The Effect of Intervening Tax Avoidance on Leverage on Firm Value - Wijaya, Melinda; Bernawati, Yustrida (E-Jurnal Akuntansi; Vol 31 No 1 (2021), 2021)
This study aims to prove the effect of leverage on firm value empirically using tax avoidance as an intervening variable. This study uses company objects listed on the Indonesia Stock Exchange. The research sample used was 66 manufacturing companies listed on the Indonesia Stock Exchange for 2016-2018, which were selected by purposive sampling method, and the number of sample data was 198 data. The firm value variable is measured by price to book value, which was tested using linear regression using SPSS 23 and path analysis. The test results show that: (1) leverage has a significant effect on tax avoidance. (2) leverage and tax avoidance have a significant effect on firm value. (3) the tax avoidance variable cannot be proven as a variable that mediates leverage and firm value. Keywords: Leverage; Tax Avoidance; Firm Value.